ORIENTASI MASYARAKAT KOTA BOGOR TERHADAP NILAI KENYAMANAN UDARA - Andry Saputra; Ricky Avenzora; Dudung Darusman; Rachmad Hermawan (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2016)
Public participation is needed to answer the limitation of fund in realizing the micro-climate amelioration program. This research aims to analyze the public perception on climate change in Bogor City, the air amenity index on micro-climate, and the value of willingness to pay (WTP) of community. Data was collected through questionnaires using One Score One Criteria method (Avenzora, 2008) and result was analyzed using statistics. The research showed that each village facing different problems related to the causes of the air amenity degradation. This result was also supported by the value of Temperature Humidity Index which was uncomfortable and according to the public perception that there was an increasing of the air temperature and humidity. The value of willingness to contribute of the community was Rp12,413/family/month which is accumulatively community participation potency of Bogor City estimated to reach Rp3,220,453,546 per month.